Structual change in times of increasing openness: Assessing path dependency in European economic integration - Claudius Gräbner; Philipp Heimberger; Jakob Kapeller; Bernhard Schütz (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
This paper analyzes the dynamics of structural polarization and macroeconomic divergence in the context of European integration, where the latter is understood primarily as an increase in economic and financial openness. In the process of estimating the dynamic effects of such an openness shock on 26 EU countries, we develop a taxonomy of European economies that consists of core, periphery and catching-up countries, as well as financial hubs. We show that these four country groups have responded in a distinct way to the openness shock imposed by European integration and argue that the latter should be seen as an evolutionary process that has given rise to different path-dependent developmental trajectories. These trajectories relate to the sectoral development of European economies and the evolution of their technological capabilities. We propose a set of interrelated policy measures to counteract structural polarization and to promote macroeconomic convergence in Europe.
Keywords: 330; Europe; path dependency; European integration; economic openness; competitiveness